2020
DOI: 10.3390/antiox9030250
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Postbiotic Lactobacillus plantarum Improves Serum and Ruminal Antioxidant Activity and Upregulates Hepatic Antioxidant Enzymes and Ruminal Barrier Function in Post-Weaning Lambs

Abstract: Postbiotics from Lactobacillus plantarum have been reported to improve growth performance, nutrient utilization, immune status and gut health in livestock. However, there is scarce information on the antioxidant activity of postbiotics and its modulation of antioxidant activity and rumen barrier function in animals. We investigated the antioxidant activity of postbiotics from L. plantarum RG14, RG11 and TL1 and dietary effects in post-weaning lambs on serum and ruminal antioxidant activity, hepatic antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 54 publications
4
58
0
7
Order By: Relevance
“…Пробіотики здатні змінювати рН рубця і виробляти антибіотичні речовини для того, щоб запобігти розмноженню патогенної мікрофлори та прикріпленню її до епітелію. Так, деякі види Lactobacillus мають сильну пригнічуючу активність на L. monocytogenes, S. thypimurium та E. coli (Izuddin et al, 2019;Izuddin et al, 2020). Дослідниками були виділені органічні кислоти -як метаболіти видів.…”
Section: вступunclassified
See 2 more Smart Citations
“…Пробіотики здатні змінювати рН рубця і виробляти антибіотичні речовини для того, щоб запобігти розмноженню патогенної мікрофлори та прикріпленню її до епітелію. Так, деякі види Lactobacillus мають сильну пригнічуючу активність на L. monocytogenes, S. thypimurium та E. coli (Izuddin et al, 2019;Izuddin et al, 2020). Дослідниками були виділені органічні кислоти -як метаболіти видів.…”
Section: вступunclassified
“…Отже, включення до випоювань молока ФПД "Імунобактерин-D" 1 раз/добу, щоденно, забезпечує надійну (100 %) профілактику розладів травлення (Izuddin et al, 2020).…”
Section: рис 1 діарея у телят протягом першого місяця життя в досліunclassified
See 1 more Smart Citation
“…Aside from developing a healthy gut and promote growth performance, a preliminary study from this laboratory revealed that the postbiotics produced by L. plantarum have high antioxidant activities [40]. Similarly, bacterial cultures of L. plantarum were reported to exhibit high antioxidative activities [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been observed that the dietary supplementation of postbiotics promoted the health and growth performance in broilers [31][32][33], layers [34,35] and piglets [36,37]. More recently, postbiotics have been reported enhancing the growth performance, rumen fermentation, immune status, antioxidant defence system, and gut health in small ruminants [38][39][40]. Under normal environmental temperature, dietary supplementation of postbiotics improved health and growth performance of broilers by promoting their immune status, growth genes expression and gut health as their supplementation significantly improved the intestinal villus, decreased the population of Enterobacteriaceae and faecal pH, and increased the population of lactic acid bacteria [25,[31][32][33]41].…”
Section: Introductionmentioning
confidence: 99%